Order Imbalances and Stock Price Movements on October 19 and 20, 1987 - BLUME, MARSHALL E.; MACKINLAY, A. CRAIG; TERKER, BRUCE (Journal of Finance, 1989)
ABSTRACT On October 19, 1987, NYSE stocks in the S&P index declined seven percentage points more than NYSE stocks not in this index. In the first hour of trading on October 20, the S&P stocks virtually recovered to the level of the non‐S&P stocks. There is a strong relation between order imbalances and stock price movements, both in analyses of time series and cross‐sections. Thus, in addition to the breakdown in the linkage between future prices and the spot index on these two days, there were also breakdowns in the linkage among NYSE stocks.